Adherence to Child Attention-Deficit/Hyperactivity Disorder Treatment Guidelines in Medical Homes—Results from a National Survey. Issue 9 (December 2021) - AlRasheed, Rashed M.; Martin-Herz, Susanne P.; Glidden, David V.; Okumura, Megumi J.
ABSTRACT: Objective: Having primary care delivered through a medical home is believed to improve mental health care delivery to children. Children with attention-deficit/hyperactivity disorder (ADHD) are commonly treated in pediatric practices, yet little is known about ADHD treatment patterns in medical homes. Our objective was to assess for treatment variation depending on parent-perceived medical home (PPMH) status. We hypothesized that having a PPMH would be associated with receiving ADHD treatments recommended by clinical guidelines. Methods: We used the 2016 National Survey of Children's Health—a nationally representative cross-sectional survey of children in the United States. Analyses included an unweighted sample of 4, 252, representing 5.4 million children aged 3 to 17 years with parent-reported ADHD. Child characteristics were analyzed using descriptive statistics. Associations between ADHD treatment types and PPMH status were assessed using a multinomial logistic regression, adjusting for child characteristics. Results: Having a PPMH was associated with increased prevalence odds of children's receipt of medications alone for ADHD (vs no treatment). The prevalence odds of receiving behavioral treatment alone (vs medications alone) for ADHD decreased by 43% when children had a PPMH (95% confidence interval, 0.38–0.85, p = 0.01). PPMH status was not associated with a statistically significant difference in prevalence odds of receiving combination treatment (vs medications alone) for pediatric ADHD. Conclusion: Having a PPMH was associated with children's receipt of ADHD medications alone, but not behavioral treatments. Our findings suggest that medical homes may need further improvement to ensure that children with ADHD receive treatments as recommended by clinical guidelines.